MiR-30c-5p regulates macrophage-mediated inflammation and pro-atherosclerosis pathways. Issue 13 (14th August 2017) - Ceolotto, Giulio; Giannella, Alessandra; Albiero, Mattia; Kuppusamy, Maniselvan; Radu, Claudia; Simioni, Paolo; Garlaschelli, Katia; Baragetti, Andrea; Catapano, Alberico Luigi; Iori, Elisabetta; Fadini, Gian Paolo; Avogaro, Angelo; et al.
Abstract: Aims: Atherosclerosis is an inflammatory disease wherein cholesterol-loaded macrophages play a major role. MicroRNAs and microparticles propagate inflammatory pathways and are involved in cardiovascular disease. We aimed to screen and validate circulating microRNAs correlated with atherosclerosis development in humans, and to dissect the molecular mechanisms associated with atherogenesis using in vitro and in vivo approaches. Methods and results: A panel of 179 secreted microRNAs was screened in plasma samples of patients with and without atherosclerosis, and validated cross-sectionally and prospectively in patients followed for up to 11 years. miR-30c-5p was inversely correlated with total and LDL cholesterol, carotid intimal media thickness (CIMT), presence and future development of plaques. Using a human macrophage line and in vitro gene silencing strategies, we found that miR-30c-5p was downregulated by oxidized LDL (oxLDL) via the scavenger receptor CD36 and inhibition miR processing by Dicer. In turn, miR-30c-5p downregulation was responsible for the effects of oxLDL on macrophage IL-1β release, caspase-3 expression, and apoptosis. miR-30c-5p loaded into microparticles was uptaken by macrophages and regulated target genes, like caspase-3, at transcriptional level. To establish the relevance of this pathway on endothelial damage as the earliest step of atherogenesis, we show that systemic miR-30c-5p knockdown induced caspase-3 and impaired endothelial healing after carotid injury in C57Bl/6 J mice. Conclusions: With an unbiased screening of secreted microRNAs, we identify reduction of miR-30c-5p in microparticles as a promoter of early atherosclerosis, by conveying pro-inflammatory pro-apoptotic signals and impairing endothelial healing. Therefore, stimulation of miR-30c-5p is a candidate direct anti-atherosclerotic therapy.